Thomas J. Staudt letter to Nicholas S. Halmi regarding bird sightings - Staudt, Thomas J.et al (1977)
Letter from Thomas J. Staudt to Nicholas S. Halmi regarding bird sightings in the Iowa City area. Notes discussing sightings of a Carolina Wren and a Pine Grosbeak are noted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter, 1977-1978. Epson - sheet feed/flatbed